Pemphigus vegetans: A clinical case - A. E. Karamova; V. V. Chikin; L. F. Znamenskaya; M. A. Nefedova; E. S. Mamedova (State Scientific Center of Dermatovenereology and Cosmetology, 2019)
Aim. To present a clinical case of pemphigus vegetans, a rare form of dermatosis.Materials and methods. A clinical and laboratory examination of a 32-year-old woman complaining of rash was carried out. The rash in the form of blisters, pustules, erosions and vegetating lesions was located mainly on the mucous membranes and skin folds. The list of performed examinations included a cytological study of a swab taken from the bottom of a lesion, a histological examination of skin biopsies from a lesion and an immunofluorescence study of biopsy specimens taken from an apparently non-affected skin area.Results. The clinical manifestations of the disease and the results of the conducted histological examinations corresponded to the diagnosis of pemphigus vegetans. The diagnosis was confirmed by the presence of acantholytic cells in the swab and IgG deposits in the intercellular spaces of the epidermis. Oral therapy with prednisone at a dose of 1 mg/kg body weight per day led to regression of the rash.Conclusion. In the investigated clinical case, the localization and nature of skin lesions were typical of pemphigus vegetans. The conducted histological and enzyme immunoassays confirmed the diagnosis, which allowed an adequate therapy to be selected. As a result, the patient demonstrated a pronounced clinical improvement. The described case is presented due to the rarity of this dermatosis.